Cost-Effective Screening for Breast Cancer Worldwide: Current State and Future Directions - A. Sarvazyan; V. Egorov; J.S. Son; C.S. Kaufman (Breast Cancer: Basic and Clinical Research, 2008)
Affordability of healthcare is highly limited by its skyrocketing cost. Access to screening and diagnostic medical equipment and medicine in developing countries is inadequate for the majority of the population. There is a tremendous worldwide need to detect breast cancer at its earliest stage. These needs must be balanced by the ability of countries to provide breast cancer screening technology to their populations. We reviewed the diagnostic accuracy, procedure cost and cost-effectiveness of currently available technique for breast screening and diagnosis including clinical breast examination, mammography, ultrasound, magnetic resonance imaging, biopsy and a new modality for cancer diagnostics termed elasticity imaging that has emerged in the last decade. Clinical results demonstrate that elasticity imaging even in its simplest and least sophisticated versions, like tactile imaging, has significant diagnostic potential comparable and exceeding that of conventional imaging techniques. In view of many countries with limited resources, effective yet less expensive modes of screening must be considered worldwide. The tactile imaging is one method that has the potential to provide cost-effective breast cancer screening and diagnostics.